2015
DOI: 10.1039/c5np00032g
|View full text |Cite
|
Sign up to set email alerts
|

Simple indole alkaloids and those with a nonrearranged monoterpenoid unit

Minoru Ishikura,
Takumi Abe,
Tominari Choshi
et al.

Abstract: This review covers the literature on simple indole alkaloids and those with a nonrearranged monoterpenoid unit from the beginning of 2012 up to the end of 2013, which includes newly isolated alkaloids, structure determinations, total syntheses and biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(61 citation statements)
references
References 337 publications
(384 reference statements)
1
60
0
Order By: Relevance
“…products. [1] These compounds have attracted tremendous interest from the synthetic community as ar esult of their diverse biological activities as well as their challenging molecular architectures. [2] In particular spiroindoline alkaloids ( Figure 1) have garnered much attention, as demonstrated by the high number of approaches to construct the spirocyclic unit.…”
Section: Indolealkaloidsconstitutealargeanddiverseclassofnaturalmentioning
confidence: 99%
“…products. [1] These compounds have attracted tremendous interest from the synthetic community as ar esult of their diverse biological activities as well as their challenging molecular architectures. [2] In particular spiroindoline alkaloids ( Figure 1) have garnered much attention, as demonstrated by the high number of approaches to construct the spirocyclic unit.…”
Section: Indolealkaloidsconstitutealargeanddiverseclassofnaturalmentioning
confidence: 99%
“…the Fischer, Bischler, Reissert, and Madelung indole syntheses), were developed, several of which are still widely used today . The interest in this “privileged scaffold” originates in part from the numerous naturally occurring bioactive indole alkaloids (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…It has been further demonstrated that alkaloids are the main bioactive components responsible for therapeutic efficacy of Kumu and its preparations for their potent activities against infection and abscesses of the respiratory, digestive, and urinary systems [13,14,15,16,17,18]. Up to now, more than sixty β -carboline and canthinone alkaloids have been isolated from P. quassioides , including nigakinone (5-hydroxy-4-methoxycanthin-6-one), 4,5-dimethoxycanthin-6-one, 3-methylcanthin-5,6-dione, β -carboline-1-carboxylic acid, β -carboline-1-propanoic acid, and so on.…”
Section: Introductionmentioning
confidence: 99%